Executives Sometimes Lose it, Just Like the Rest of Us - Hambrick, Donald C.; Finkelstein, Sydney; Mooney, Ann C. (Academy of Management Review, 2005)
In our conceptualization of executive job demands, we sought to integrate a diverse body of literature from strategy, organization theory, and organizational behavior. Ganster suggests that such an integration of ideas is highly welcome but also incomplete. We build on several of Ganster's key points to further clarify the executive job demands construct, and we expand the range of possible research questions that come out of a more complete integration of ideas from the macro and micro spheres of organizational science.